Technology Usage Strategy And Distribution Channel In Increasing Customer Satisfaction From Service Offerings Available In The Marketplace (Go International): Strategi penggunaan teknologi (Technology Usage) dan Saluran Distribusi dalam meningkatkan kepuasan pelanggan dari layanan jasa yang terdapat di marketplace Indonesia (Go Internasional) - Kenny; Sri Rezeki (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This research is motivated by the challenges in ensuring customer satisfaction with marketplace services, which are still hindered by gaps in users' digital literacy, the complexity of distribution channels, and various conditions of logistics infrastructure in different regions. This study aims to evaluate the extent to which technology usage strategies and the effectiveness of distribution channels can contribute to increasing consumer satisfaction levels in marketplace based on service offerings. The research method used is descriptive quantitative, with data collected through an online questionnaire sent to marketplace users, which is then analyzed using PLS SEM to test the strength and significance of the influence between variables. The main results indicate that both research variables significantly affect customer satisfaction, with a stronger contribution coming from the distribution channels. In conclusion, strategies for technology use and the effectiveness of distribution channels both contribute to increasing customer satisfaction in service marketplace. The implications of this research emphasize that increasing customer satisfaction in the marketplace cannot be achieved solely by updating the interface in digital use or accelerating the delivery process separately, but rather requires synergy between technology use strategies and a well-functioning distribution channel network.